The Rat Mammary Gland as a Novel Site of Expression of Melanin-Concentrating Hormone Receptor 1 mRNA and Its Protein Immunoreactivity - Battagello, Daniella S.; Lorenzon, Aline R.; Diniz, Giovanne B.; Motta-Teixeira, Lívia C.; Klein, Marianne O.; Ferreira, Jozélia G. P.; Arias, Carlos M.; Adamantidis, Antoine; Sita, Luciane V.; Cipolla-Neto, José; Bevilacqua, Estela M. A. F.; Sawchenko, Paul E.; et al. (Frontiers in Endocrinology, 2020)
Lactation is a complex physiological process, depending on orchestrated central and peripheral events, including substantial brain plasticity. Among these events is a novel expression of pro-melanin-concentrating hormone (Pmch) mRNA in the rodent hypothalamus, such as the ventral part of the medial preoptic area (vmMPOA). This expression reaches its highest levels around postpartum day 19 (PPD19), when dams transition from lactation to the weaning period. The appearance of this lactation-related Pmch expression occurs simultaneously with the presence of one of the Pmch products, melanin-concentrating hormone (MCH), in the serum. Given the relevance of the MPOA to maternal physiology, and the contemporaneity between Pmch expression in this structure and the weaning period, we hypothesized that MCH has a role in the termination of lactation, acting as a mediator between central and peripheral changes. To test this, we investigated the presence of the MCH receptor 1 (MCHR1) and its gene expression in the mammary gland of female rats in different stages of the reproductive cycle. To that end, in situ hybridization, RT-PCR, RT-qPCR, nucleotide sequencing, immunohistochemistry and western blotting were employed. While Mchr1 expression was detected in the epidermis and dermis of both diestrus and lactating rats, parenchymal expression was exclusively found in the functional mammary gland of lactating rats. The expression of Mchr1 mRNA oscillated through lactation period and reached its maximum in PPD19 dams. Presence of MCHR1 was confirmed with immunohistochemistry, with preferential location of MCHR1 immunoreactive cells in the alveolar secretory cells. As was the case for gene expression, the MCHR1 protein levels were significantly higher in PPD19 than in other groups. Our data demonstrate the presence of an anatomical basis for the participation of MCH peptidergic system on the control of lactation through the mammary gland, suggesting that MCH could modulate a pro-lactation action in early postpartum days and the opposite role at the end of the lactation.